ANALISIS RESILIENSI KOMUNITAS SAMIN DAN MASYARAKAT SEKITAR KECAMATAN BANJAREJO DALAM MENGHADAPI KEKERINGAN TAHUN 2020 - Sari, Meylita Diah Anggita; Yusup, Yasin; Ajar, Seno Budhi (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2022)
The Samin community has local wisdom related to drought disaster management. The areas studied in this research are Klopoduwur Village and Sendanggayam Village, with the research objectives (1) to determine the resilience of the samin community and the community around the Banjarejo sub-district, (2) to determine the resilience level of the samin community and the surrounding community in Banjarejo sub-district. The research design used qualitative analysis using the methods of observation, interviews, and documentation with data-flow model analysis techniques. The population in this study is the community in Banjarejo District by taking samples using purposive sampling. The results showed that the resilience of the samin community and the community outside of the samin in Banjarejo District to drought disasters had medium and high resilience with absorption, adaptive, and transformative capacities applied before the drought occurred. While the form of the resilience of the samin community in Klopoduwur Village and people outside the samin community in Sendaggayam Village, Banjarejo District, against drought disasters in the form of social systems, ecological systems, and socio-ecological systems.